2011
DOI: 10.1007/s12284-011-9063-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of OsSUT2 Expression and Regulation in Germinating Embryos of Rice Seeds

Abstract: OsSUT2 encodes a putative sucrose transporter containing 12 transmembrane domains in rice plants. Subcellular localization of the OsSUT2::GFP fusion protein indicated that OsSUT2 is a cell membrane protein. In embryos of germinating seeds, the expression of OsSUT2 gradually increased during the early germinating stage. The developmental regulations of OsSUT2 in germinating embryos could be mediated by sugars transported from endosperms. OsSUT2 expression was up-regulated by glucose through a hexokinase-indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…SUT family members in many plant species are divergent in function and deferentially expressed in different tissues types or at different plant developmental stages. For instance, in rice, OsSUT1 expression has been detected in germinated seeds, leaf blades, leaf sheaths and panicles [ 14 16 ]; the expressions of both OsSUT3 and OsSUT5 are dramatically lower in embryos than those of OsSUT1 , OsSUT2, and OsSUT4 [ 17 ]; OsSUT4 has been detected in most tissues such as roots, leaves, and panicles [ 11 ], and could play a role in sucrose loading into the sheath phloem of the upper leaves during the post-heading period for sucrose transport to developing grains [ 18 ]. In Arabidopsis [ 10 ], AtSUC2 has been detected in phloem and companion cells in source leaves [ 19 , 20 ] and functions in loading sucrose into the phloem sieve elements (SEs), correspond with the result identified by tissue-specific complementation of different promoters [ 7 , 21 ] and by 14 C labeling studies [ 22 ]; AtSUC3 and AtSUC4 are expressed in minor veins of source leaves of mature plants [ 23 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…SUT family members in many plant species are divergent in function and deferentially expressed in different tissues types or at different plant developmental stages. For instance, in rice, OsSUT1 expression has been detected in germinated seeds, leaf blades, leaf sheaths and panicles [ 14 16 ]; the expressions of both OsSUT3 and OsSUT5 are dramatically lower in embryos than those of OsSUT1 , OsSUT2, and OsSUT4 [ 17 ]; OsSUT4 has been detected in most tissues such as roots, leaves, and panicles [ 11 ], and could play a role in sucrose loading into the sheath phloem of the upper leaves during the post-heading period for sucrose transport to developing grains [ 18 ]. In Arabidopsis [ 10 ], AtSUC2 has been detected in phloem and companion cells in source leaves [ 19 , 20 ] and functions in loading sucrose into the phloem sieve elements (SEs), correspond with the result identified by tissue-specific complementation of different promoters [ 7 , 21 ] and by 14 C labeling studies [ 22 ]; AtSUC3 and AtSUC4 are expressed in minor veins of source leaves of mature plants [ 23 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…CIN is involved in early seedling development, inflorescence differentiation, and grain filling in plants (Roitsch 1999;Hirose et al 2002;Cho et al 2005;Ji et al 2005;Wang et al 2008Wang et al , 2010. SUT was found to have similar functions as CIN; it was also related to seed development and plant growth (Kaur et al 2000;Scofield et al 2007;Chen et al 2010;Siao et al 2011;Siahpoosh et al 2012). However, the effects of these sucrose metabolism-related genes during cell culture under osmotic stress treatment in rice are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In germinating embryos, OsSUT1 expression was upregulated by gibberellic acid and repressed by abscisic acid (ABA) (Chen et al 2010). According to the analysis of OsSUT2 promoter::β-glucuronidase expression in transgenic rice, OsSUT2 was highly expressed in leaf mesophyll cells, lateral roots, seed coats, fertilized seeds, embryos and aleurone layers (Eom et al 2011;Siao et al 2011). Expression of the OsSUT4 gene in rice leaf tissues was observed in our previous study, and the results showed that OsSUT4 expression in the leaf sheaths of upper leaves was highly correlated with the sink/source status of tissues during heading periods (Chen and Wang 2008).…”
Section: Introductionmentioning
confidence: 99%